2017
DOI: 10.1088/1748-605x/aa785d
|View full text |Cite
|
Sign up to set email alerts
|

Substrates with patterned topography reveal metastasis of human cancer cells

Abstract: In this study, we aimed at studying the effects of engineered and patterned substrates on the migration characteristics of mammalian cancer cell lines. On the shallow topographical patterns, cells from different histological origins showed different migration speed and directionality. We also observed that cells from the same origin showed distinctive behaviour, suggesting these substrate topographies could distinguish cancer subtypes. To eliminate the influence of genetic background, we examined two isogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 72 publications
(84 reference statements)
3
15
0
Order By: Relevance
“…Hence, NP460 cells with and without TGF-β1 treatment responded differently in the 3D microenvironment. These results are consistent with our previous work that demonstrated different migration behaviors for cells in difference metastasis status when seeded on platforms with different topographies [12]. It is suggested that the topographical structure of the scaffold platforms provided more edges for cell attachment and focal adhesion formation, which favors cell movement [37,38].…”
Section: Migration Speed and Directionality Of Np460 Cells On Scaffolsupporting
confidence: 92%
See 2 more Smart Citations
“…Hence, NP460 cells with and without TGF-β1 treatment responded differently in the 3D microenvironment. These results are consistent with our previous work that demonstrated different migration behaviors for cells in difference metastasis status when seeded on platforms with different topographies [12]. It is suggested that the topographical structure of the scaffold platforms provided more edges for cell attachment and focal adhesion formation, which favors cell movement [37,38].…”
Section: Migration Speed and Directionality Of Np460 Cells On Scaffolsupporting
confidence: 92%
“…Migration behaviors of cultured cells on 2D platforms with different engineered topographies have been studied extensively [11]. We and others have demonstrated that cell culturing environment can be fabricated with different topographies [12]. Engineered platforms with confined microchannels have been fabricated using polyacrylamide hydrogel with extracellular matrix (ECM) proteins conjugated to control the stiffness and provide biochemical ligands for cell adhesion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond cell survival, topographic patterning of microscale features can influence cell migration and cytoskeletal composition. MDA-MB-231 cells had the greatest migration and cell speed on the arc pattern compared with grating pattern or flat control surface (Zhou et al, 2017). The uneven pattern of the arcs could create uneven vinculin focal adhesion protein expression within the cell, possibly causing the increased migration.…”
Section: Substrate Surface Patternsmentioning
confidence: 99%
“…It is a primary cellular process that occurs continuously, sometimes leading to the progression of pathogenic diseases [22]. Previous studies reported cell migration behaviors on two-dimensional (2D) platforms with various engineered topographies [23][24][25][26][27][28][29][30]. However, 2D models do not accurately represent the microenvironment of tumors in vivo.…”
Section: Introductionmentioning
confidence: 99%